Effectiveness of antenatal exercise intervention using behavioral theory on exercise adherence among antenatal women: research protocol - Md Yunus, Nur Farhana; Abdul Manaf, Rosliza; Abd Kadir, Hayati; Ismail, Suriani; Alagirisamy, Parwathi (Atlantis Press International, 2022)
Antenatal exercise (ANE) is one of physical activity recommended for antenatal women as the benefits outweigh the risks. Despite knowing the benefits of exercises, most antenatal women are less active during pregnancy. Addressing women’s attitude and barriers to exercise are crucial in designing intervention, it should be facilitated by a theory. Hence, this study aims to investigate the effectiveness of antenatal exercise intervention using behavioral theory on exercise adherence among antenatal women. This study will be a cluster randomized controlled trial (CRCT) in six primary health clinics with total sample estimation is 322. A two arm CRCT will be applied, a control group will be received standard antenatal care only while intervention group will be received 12 weeks ANE intervention and standard antenatal care. The ANE intervention module based on behavioral theory is the main study instrument, questionnaires on exercise adherence, perceived benefits, perceived barriers, exercise self-efficacy and HRQOL will be used in this study. Repeated measures logistic regression analysis using generalized estimating equations (GEE) will be used to evaluate the odds ratios of dependent variables between the groups at three-time points. All statistical tests are based on two-tailed test and the level of significance, alpha (α) is set at 0.05. The expected findings of this study will be a significant difference on dependent variables in intervention than control group at two time point post intervention. It could also improve antenatal women’s adherence towards ANE, hence promote active lifestyles and reduce maternal implications.